Sunnah dan Kedudukan Muhammad dalam Pandangan Muhammad Syaḥrūr - Anshori, Muhammad (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
This article discusses on contextualist understanding about sunnah or hadith. One of the contemporary Muslim thinker who is studied by muslim scholars is Muḥammad Syaḥrūr. According to Syaḥrūr, the sunnah was the initial ijtihad of Muhammad to overcome the problems that existed at that time, so it must be dynamic. Among the interesting thoughts of Syaḥrūr is his division of the concept of Muhammad's obedience and position. There are two forms of obedience to Muhammad: obedience that is not directly related to Allah (al-thā'ah al-munfashilah) and directly related to Allah (al-thā'ah al-muttashilah). In examining the hadith of the Prophet, Syaḥrūr did not understand in a textuality, but he studied the position of Muhammad when the hadith was spoken. He divided the position of Muhammad into three poins; as human beings, the Prophet, and the Apostle. The Hadith or Sunna will be universally applicable when Muhammad is based as an Apostle. Syaḥrūr's understanding of a hadith is very humanity because he is not directed to sanad studies, but rather to matan hadith.